Estimasi Proporsi Kesalahan Fonologi Pada Anak Pendidikan Anak Usia Dini (PAUD) Usia 3-5 Tahun Di Surakarta - R Asto Soesyasmoro; Anggi Resina Putri (Poltekkes Kemenkes Surakarta, 2019)
Background: In providing education about everything a child should have from an early age does not have to do with the way parents are educating. It is related to her parents in everyday life and the background factors that color children's parents, whether related to the environment of her family, religion, culture, economics or the background of the education of the elderly. From the explanation it is obvious that parents play a very important role in the formation of child social behavior.The purpose of this research aims to determine the relationship of parental education level with the ability of phonology articulation in children aged 4-5 years in TK Sri Juwita Hanum Surakarta. Methods: Uses quantitative research with a correlational descriptive design. The research population is parents and students of TK Sri Juwita Hanum Surakarta with 30 samples of research samples. Data collection techniques by filling out questionnaires. Variable-free research i.e. the level of parental education and bound variables is the ability of phonological articulation in children aged (4-5 years). The statistical test used was Chi Square correlation test. Result: there is a positive and significant relationship between the level of parental education and the ability of phonology articulation in children aged 4-5 years in TK Sri Juwita Hanum Surakarta. Things his show with a p value of 0.013.Conclusion: of parental education affects the development of articulation in preschool age children (4-5 years old). A positive relationship means the higher the parent's education, the greater the influence on its phonological articulation ability. When children grow and develop both physically and mentally.